INTERNATIONAL COOPERATION AND FRICTION IN MARITIME SECURITY OPERATIONS - Jason Kelshall (The Journal of Intelligence, Conflict and Warfare)
On November 18th, 2024, Commander Jason Kelshall presented International Cooperation and Friction in Maritime Security Operations for this year’s West Coast Security Conference. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the challenges of combating illicit maritime trade, transnational organized crime, and environmental crimes within the framework of SEACOP VI.